Upaya Ikatan Remaja Masjid Jami Nurul A’la dalam Mencegah Kenakalan Remaja di Jatiluhur Jatiluhur Jatiasih Bekasi - Faizah, Faizah; Lubis, Zulkifli; Fadhil, Abdul (Jurnal Studi Al-Qur'an, 2017)
This study aims to describe and analyze attempts Youth Association the Jami Mosque Nurul A'la in preventing juvenile delinquency, programs conducted by Irmana in preventing juvenile delinquency. In this study, the approach taken is through a qualitative approach. Results of this study indicate that the Youth Association the Jami Mosque Nurul A'la have succeeded in preventing juvenile delinquency Jatilahur Jatiasih Bekasi area is to encourage the youth to participate in positive activities held Irmana, such as holding lectures, reviewing books, orphans , charity, and fasting together. Through several activities that teenagers who behave inappropriately, changing gradually into a better direction.